2021
DOI: 10.2147/nss.s331880
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Sudden Sensorineural Hearing Loss in Patients with Obstructive Sleep Apnea

Abstract: Purpose: Obstructive sleep apnea (OSA) is characterized by recurring hypoxic-apneic events during sleep, and labyrinthine vascular compromise is a pathophysiologic hallmark of idiopathic sudden sensorineural hearing loss (ISSNHL). Some reports have discussed the relationship between OSA and hearing impairment; however, few have examined hearing prognosis in OSA and patients without OSA with ISSNHL. We aimed to investigate clinical manifestations of ISSNHL in patients with OSA, including severity of hearing los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Most previous studies have suggested that sleep disturbance is a potential risk factor for sudden HL. 40 41 Sleep disturbance can cause negative emotions, such as anxiety and depression, which may affect the hearing of patients. 42 Animal and human studies have demonstrated that repeated sleep deprivation potentially aggravates noise-induced damage to the outer and inner hair cells of the cochlear basal gyrus synaptic band, thus reducing the ability of the cochlea to transcode sound.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have suggested that sleep disturbance is a potential risk factor for sudden HL. 40 41 Sleep disturbance can cause negative emotions, such as anxiety and depression, which may affect the hearing of patients. 42 Animal and human studies have demonstrated that repeated sleep deprivation potentially aggravates noise-induced damage to the outer and inner hair cells of the cochlear basal gyrus synaptic band, thus reducing the ability of the cochlea to transcode sound.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with the results of Bai et al, [ 13 ] whose NAC group (which received concurrent intratympanic steroid injection therapy and oral NAC) showed a significant hearing gain at 8 kHz in comparison to the control group treated with intratympanic steroid injection therapy alone. Chen et al [ 15 ] reported that the hearing threshold of the affected ear improved after steroid therapy at all frequencies, except 8 kHz, in patients with obstructive sleep apnea, which also confirmed the damaging effect of hypoxia on high-frequency hearing. The association between the use of the antioxidant NAC and hearing gain at higher frequencies suggests region-specific susceptibility to oxidative stress in the cochlea.…”
Section: Discussionmentioning
confidence: 83%
“…The therapeutic effects of steroids, taken orally or administered by intratympanic injection, are widely known, so recovery of hearing in both the NAC and non-NAC groups was expected. Chen et al [ 15 ] also reported that steroids have potent antiinflammatory effects, so effective improvement in the hearing threshold of the affected ear after steroid treatment was not surprising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior study reported poorer responses to steroid treatment for the improvement of hearing in patients with OSA and idiopathic sudden sensorineural hearing loss (ISSNHL) than patients without OSA. It was indicated that OSArelated hypoxia and snoring noise is hazardous to hearing and standard treatments with CPAP is suggested in OSA patients for both holistic and auditory health [22]. The rat experiment also proved the combination of noise and hypoxia will lead to 70-100% loss of outer hair cells in the high-frequency coding region, and even some loss of inner hair cells.…”
Section: Plos Onementioning
confidence: 99%